Hermitian self-dual abelian codes - Jitman, Somphong (2014)
Hermitian self-dual abelian codes in a group ring Fq2 [G], where Fq2 is a finite field of order q2 and G is a finite abelian group, are studied. Using the well-known discrete Fourier transform decomposition for a semi-simple group ring, a characterization of Hermitian self-dual abelian codes in Fq2 [G] is given, together with an alternative proof of necessary and sufficient conditions for the existence of such a code in Fq2 [G], i.e., there exists a Hermitian self-dual abelian code in Fq2 [G] if and only if the order of G is even and q = 2l for some positive integer l. Later on, the study is further restricted to the case where F22l [G] is a principal ideal group ring, or equivalently, G = A Z2k with 2 - jAj. Based on the characterization obtained, the number of Hermitian self-dual abelian codes in F22l [A Z2k ] can be determined easily. When A is cyclic, this result answers an open problem of Jia et al. concerning Hermitian self-dual cyclic codes. In many cases, F22l [A Z2k ] contains a unique Hermitian self-dual abelian code. The criteria for such cases are determined in terms of l and the order of A. Finally, the distribution of finite abelian groups A such that a unique Hermitian self-dual abelian code exists in F22l [A Z2] is established, together with the distribution of odd integers m such that a unique Hermitian self-dual cyclic code of length 2m over F22l exists.